STRATEGI PENANGANAN PADA ANAK DENGAN KASUS DEFISIT PERHATIAN - Siti Khadijah; Silvia Rahmani; Ratna Faeruz (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This study aims to determine the behavior of ADHD children in and out of class, as well as how to handle ADHD children at RA Al-Hilal 02 Cikarang Utara. This study uses a qualitative approach with a case study research type. Data collection techniques in this study were carried out by observation, interviews and documentation methods which were then triangulated to obtain valid data. The results of the study found that RA Al-Hilal 02 provides various treatments for ADHD children according to their needs, including the type of IEP or Individualized Education Program service by first observing their needs. IEP service is one of the treatments given with the aim of creating a sense of self-confidence in children and the rights of children to pursue quality and optimal education so as to reduce dropout rates. The results of the study show that there are 15 types of ADHD child behavior during learning in class that require treatment so as not to interfere with the effectiveness of learning. Of the 15 types of behavior, they are classified into 3 types of barriers, namely concentration barriers, self-control and hyperactivity. Some of the handling strategies carried out by teachers are quite varied, where there are 19 types of teacher strategies in dealing with ADHD child behavior in class starting from 2 steps at the identification stage, 2 steps at the planning stage, 11 steps at the implementation stage, 2 steps at the evaluation stage, and 2 steps at follow-up stage.